é€šè¿‡è¯¾æ–‡ä¸Žç”Ÿè¯åˆ†æžã€ŠæˆåŠŸä¹‹è·¯ã€‹åˆçº§ç»¼åˆè¯¾æ•™æ - Fransiska, Rica; Thamrin, Lily; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
The aim of this research is to know framework/principle of "Road To Success" comprehensive textbooks about writing style and to know its uses in primary grade students of Chinese Language Department, Pedagogical Institute at Tanjungpura University. This research using literature study focuses on article genre, content, vocabulary number and difficulty level, using survey to usersâ€™ textbook evaluation, and using questionnaires for students and interviews for students and teachers. Through this research, it is found that the textbooks meet the scientific principles in foreign mandarin language of textbooks writing style, fullfil the learning needs of students, and is a valuable teaching materials for the teachers. It is expected that this research can become a consider and reference for foreign mandarin language teaching especially on Indonesianâ€™s primary grade comprehensive textbooks. Keywords: Textbooks, Article, Vocabulary, EvaluationÂ æ‘˜è¦:ä¸ºå¾—çŸ¥ã€ŠæˆåŠŸä¹‹è·¯ã€‹åˆçº§ç»¼åˆè¯¾æ•™æçš„ç¼–å†™ä½“ä¾‹å’Œä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦ä¸æ–‡ç³»ä½¿ç”¨è¯¥æ•™æçš„æƒ…å†µï¼Œæœ¬æ–‡é€šè¿‡åˆ†æžè¯¾æ–‡è¯¾æ–‡ä¸Žç”Ÿè¯ï¼Œå¯¹è¯¥æ•™æçš„è¯¾æ–‡ä½“è£ã€å†…å®¹ï¼Œç”Ÿè¯é‡ã€ç‰çº§ç”¨æ–‡çŒ®ç ”ç©¶æ³•è¿›è¡Œæ–‡çŒ®ç ”ç©¶ï¼Œå¹¶å¯¹è¯¥æ•™æçš„ä½¿ç”¨è€…è¿›è¡Œè°ƒæŸ¥ï¼šå¯¹å¦ç”Ÿè¿›è¡Œé—®å·è°ƒæŸ¥ä¸Žè®¿è°ˆï¼›é’ˆå¯¹æ•™å¸ˆè¿›è¡Œè®¿è°ˆã€‚ç ”ç©¶ç»“æžœæ˜¾ç¤ºï¼Œã€ŠæˆåŠŸä¹‹è·¯ã€‹åˆçº§ç»¼åˆè¯¾æ•™æç¬¦åˆå¯¹å¤–æ±‰è¯æ•™æç¼–å†™çš„ç§‘å¦æ€§åŽŸåˆ™ï¼Œä¹Ÿç¬¦åˆå¦ç”Ÿçš„å¦ä¹ è¦æ±‚å¹¶æœ‰åˆ©äºŽæ•™å¸ˆçš„æ•™å¦æŽ¢ç©¶ã€‚é€šè¿‡è¿™é¡¹ç ”ç©¶ï¼Œå¸Œæœ›æœ¬æ–‡èƒ½å¯¹å¯¹å¤–æ±‰è¯æ•™å¦å°¤å…¶å°å°¼æ˜¯åˆçº§é˜¶æ®µç»¼åˆè¯¾æ•™æçš„é€‰ç”¨æå‡ºå»ºè®®å’Œå‚è€ƒã€‚ å…³é”®è¯ï¼šæ•™æï¼›è¯¾æ–‡ï¼›ç”Ÿè¯ï¼›è¯„ä»·